Efficiency of the Inquiry Based Science Education at Primary Schools During Science Lessons with the use of School Gardens in the Czech Republic - Vácha, Zbyněk; Ditrich, Tomáš (Scientia in educatione, 2016)
The article is focused on the survey: How effective are teaching methods with elements of inquiry based science education in the area of school gardens at primary school in the Czech Republic? Data was collected through pair groups experiment. In the experimental group there were 73–75 pupils and in the control group 70–72 pupils from the fourth grade at the primary school. Results point to the fact, that inquiry based science education has statistically significant effect on learning of new knowledge as well positive effect on growing popularity of science lessons at primary school. Other results show that to be efficient, inquiry based science education must be used during lessons repeatedly. In the opposite case, inquiry based science education is difficult and too abstract for pupils at the primary school.